Development of the calculation methodology of cross-beam foundation on the sloping base complicated by karst and sinkhole processes - A. B. Barykin; B. Yu. Barykin; E. V. Zelenin (Vestnik MGSU)
Introduction. A calculation scheme of karst sinkhole in karst territories using the results of laboratory experimental studies is developed, which makes it possible to determine the shape and size of karst sinkhole depending on the karst cavity dimeter (radius), its depth, the base slope angle and the angle of internal friction of soils composing the slope.Materials and methods. The method of calculation of normal contact stresses in the sloping soil base under the bottom of the cross-beam foundation during the formation of karst sinkholes is given, considering three main cases of karst cavity location in the slope massif with the most unfavourable location of the karst cavity relative to the cross-beam foundation structures.Results. The analytical dependence allowing to determine the theoretical value of the design value of the diameter Lc of the cavity in the sloping base is obtained, as well as to establish the main design dependences for determining the normal contact stresses, which allow to estimate the changes in the VAT parameters of the cross-beam foundation operation after the cavity vault collapse and formation of a complex shape of the collapse funnel.Conclusions. The developed methodology is convenient to use for qualitative assessment of design solutions in the design of cross-beam foundations on a sloping base in karst-prone areas. The obtained variant design values of the main VAT parameters according to the proposed methodology will allow to apply rational design solutions in design.